Traumatic brain injury alters neuropsychiatric symptomatology in all‐cause dementia. Issue 4 (19th January 2021) - Bray, Michael J. C.; Richey, Lisa N.; Bryant, Barry R.; Krieg, Akshay; Jahed, Sahar; Tobolowsky, William; LoBue, Christian; Peters, Matthew E.
Abstract: Introduction: Traumatic brain injury (TBI) may alter the course of neuropsychiatric symptom (NPS) onset during dementia development. The connection among TBI, NPS, and dementia progression is of increasing interest to researchers and clinicians. Methods: Incidence of NPS was examined in participants with normal cognition who progressed to all‐cause dementia based on whether TBI history was present (n = 130) or absent (n = 849). Survival analyses were used to examine NPS incidence across 7.6 ± 3.0 years of follow‐up. Results: Participants with TBI history had increased prevalence and incidence of apathy (44.7% vs 29.9%, P = .0062; HRadj. = 1.708, P = .0018) and motor disturbances (17.2% vs 9.5%, P = .0458; HRadj. = 2.023, P = .0168), controlling for demographics and type of dementia diagnosis. Earlier anxiety onset was associated with TBI (692 days prior to dementia diagnosis vs 161 days, P = .0265). Discussion: History of TBI is associated with increased risk for and earlier onset of NPS in the trajectory of dementia development.